2013
DOI: 10.1037/a0034173
|View full text |Cite
|
Sign up to set email alerts
|

Smokers versus snorters: Do treatment outcomes differ according to route of cocaine administration?

Abstract: Smoking cocaine achieves maximal concentration and effect far more rapidly than through the intranasal (‘snorting’) route, and it is associated with greater propensity for dependence and more severe consequences. However, very little is known about differences in treatment outcome according to route of administration. This study compared treatment outcomes, such as frequency of cocaine use and Addiction Severity Index (ASI) composite scores, by primary route of cocaine administration (smoking vs. intranasal) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
21

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 68 publications
2
21
0
21
Order By: Relevance
“…Although smoked and intranasal cocaine are the two most prevalent routes of administration for naturalistic use, cocaine was delivered intravenously (IV) in these translational studies because that route is readily implemented in the monkey laboratory. In addition, the pharmacokinetic profile of the IV route more closely approximates smoked cocaine (Cone, 1995), which is the most predominant route of administration used in dependent individuals (e.g., Kiluk et al, 2013). These self-administration studies incorporated choice procedures in which a species-specific, non-drug alternative reinforcer previously shown to reduce cocaine self-administration (food in the monkeys, e.g., Huskinson et al, 2015; Nader and Woolverton, 1991; Negus, 2003; money in the humans, e.g., Greenwald et al, 2014; Higgins et al, 1994; Stoops et al, 2010a) was made available as an alternative to cocaine under concurrent progressive-ratio (PR) schedules.…”
Section: Introductionmentioning
confidence: 99%
“…Although smoked and intranasal cocaine are the two most prevalent routes of administration for naturalistic use, cocaine was delivered intravenously (IV) in these translational studies because that route is readily implemented in the monkey laboratory. In addition, the pharmacokinetic profile of the IV route more closely approximates smoked cocaine (Cone, 1995), which is the most predominant route of administration used in dependent individuals (e.g., Kiluk et al, 2013). These self-administration studies incorporated choice procedures in which a species-specific, non-drug alternative reinforcer previously shown to reduce cocaine self-administration (food in the monkeys, e.g., Huskinson et al, 2015; Nader and Woolverton, 1991; Negus, 2003; money in the humans, e.g., Greenwald et al, 2014; Higgins et al, 1994; Stoops et al, 2010a) was made available as an alternative to cocaine under concurrent progressive-ratio (PR) schedules.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this study is the only one we are aware of that examined the effects of AMPH on a range of measures as a function of preferred route of cocaine use. This is clinically relevant because smoked cocaine users have been shown to be more difficult to treat than intranasal cocaine users (Bisaga et al, 2005, 2006; Kiluk et al, 2013; Nunes et al, 1995). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Volkow et al (2000) found that ratings of “high” were the greatest for smoked cocaine and lowest for intranasal cocaine, corresponding to the onset of peak subjective effects. Route of administration is considered an important factor in the likelihood of developing a cocaine use disorder, the severity of the use disorder, and other problems associated with cocaine use (e.g., Chen and Anthony, 2004; Gossop et al, 1994; Hatsukami and Fischman, 1996), with several studies demonstrating that smoked cocaine users have less successful treatment outcomes than intranasal users (e.g., Bisaga et al, 2005; Gossop et al, 2003; Grella et al, 2003; Kiluk et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…magnitude of cocaine's effects, as caused by the route of administration, contribute to the addictiveness of cocaine (Kiluk et al, 2013). Consistent with the general characteristics of drug addiction, cocaine users can experience tolerance as well as dependence on the drug, further contributing to cocaine's addictive properties (Gardner, 2011).…”
Section: Journal Of Young Investigatorsmentioning
confidence: 96%